Étude anthropologique d’un cimetière de paroisse rurale : les sépultures (8e-19e s.) de Rigny (Rigny-Ussé, Indre-et-Loire) - Christian Theureau (Revue Archéologique du Centre de la France)
The rural cemetery of the former parochial centre of Rigny yielded 1,704 burials dating from historical periods. This good-sized sample has facilitated a useful reappraisal of basic anthropological techniques. It paints a singular picture of this rustic world which, over a long period of time, took in physically disadvantaged people and children from the neighbouring towns. Conditions of life in this milieu were sufficient to bring about certain biological improvements, especially where longevity was concerned.